Desenvolvimento e caracterização de nanopartículas lipídicas sólidas para administração cutânea de trans-resveratrol - Rigon, Roberta Balansin [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The trans-resveratrol (RES) is an important substance in prevention and treatment of skin carcinogenesis. Though, the RES has low bioavailability and rapid metabolism when it administered orally, these factors could be circumvented by its dermal administration using solid lipid nanoparticles (SLNs). The aim of this study was to develop SLN with RES for use in antitumor therapy of melanoma. SLNs composed of stearic acid (SA) or polyoxyethylene stearate (40) (PS40); poloxamer 407; soy phosphatidylcholine (SPC) and the aqueous phase were made by sonication and it were added or not of 0.1% RES. The particle size, polydispersity index (PdI) and zeta potential were analyzed by dynamic light scattering (DLS). The SLNs were analyzed by field emission gun scanning electron microscope (FEG-SEM) and differential scanning calorimetry (DSC). An analytical method using HPLC-DAD was developed to quantify the RES. In vitro release and skin permeation/retention of SLN plus RES were conducted, as well as evaluation of depigmenting potency. The results concerning the average size, PdI and zeta potential of SLNs showed that formulations consisting of polyoxyethylene stearate (40) had a lower average diameter, ~20 nm, the addition of soy phosphatidylcholine promoted increases PdI and the formulations exhibited zeta potential smaller than -6mV. The DSC analysis showed no endothermic peak of the SLN with RES. Microscopic analysis suggest that material formed has nanometer distribution. The analytical method proved satisfactory in relation to RDC n° 899/2003 for RES. The formulations had release kinetics according Weibull's models and it were permeated through the skin up to 45% after 24 hours. The formulation with RES and free RES were more effective than kojic acid in tyrosinase inhibition. The results suggest that formulations had potential for use in antitumor therapy of melanoma.
Keywords: Melanoma; Nanopartículas; Agentes antineoplasicos; Carcinogenese; Pele - Doenças; Cancer